2019
DOI: 10.3390/polym11060984
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fluorescent Molecularly Imprinted Polymers via Pickering Emulsion Interfaces and the Application for Visual Sensing Analysis of Listeria Monocytogenes

Abstract: In this work, a novel molecularly imprinted polymer (MIP) with water-soluble CdTe quantum dots (QDs) was synthesized by oil-in-water Pickering emulsion polymerization using whole Listeria monocytogenes as the template. Listeria monocytogenes was first treated by acryloyl-functionalized chitosan with QDs to form a bacteria–chitosan network as the water phase. This was then stabilized in an oil-in-water emulsion comprising a cross-linker, monomer, and initiator, causing recognition sites on the surface of micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 40 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…According to WHO (2015), almost 600 million disease cases caused by the consumption of contaminated food by pathogenic bacteria. Salmonella sp., Escherichia coli O157:H7, Staphylococcus aureus, Listeria monocytogenes, and Bacillus cereus are known pathogens in food [1,2]. Those bacteria are a threat to ready-to-eat foods.…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO (2015), almost 600 million disease cases caused by the consumption of contaminated food by pathogenic bacteria. Salmonella sp., Escherichia coli O157:H7, Staphylococcus aureus, Listeria monocytogenes, and Bacillus cereus are known pathogens in food [1,2]. Those bacteria are a threat to ready-to-eat foods.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the fluorescence intensity of PABA gradually decreased with increasing BPO concentration (Figure 5A) and the negative logarithm of BPO concentration was proportional to the quenching in PABA fluorescence intensity (F 0 –F i ) with a linear relationship of Y = −198.94 X + 1819.44 (R 2 = 0.9941) in the detection range of 8.26 × 10 −9 M – 8.26 × 10 −4 M (Figure 5B). The LOD is usually obtained from three times of signals to noise (S/N = 3) [8,35,36,37,38] and the estimated LOD was 1.06 × 10 −9 M, featuring a high sensitivity. With the developed method, the ultrasensitive detection for BPO can be completed within a short time.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the obtained polymers are eluted under appropriate conditions to elute the template molecules. Thus, molecularly imprinted polymers with imprinted holes matched with the size, shape, and functional groups of the template molecules are obtained [1,2]. Pauling, a famous scholar, put forward the theory of antibody formation in the 1940s, which laid a theoretical foundation for the generation of molecular imprinting technology [3].…”
Section: Introductionmentioning
confidence: 99%